Stability of Soft Constrained Finite Horizon Model Predictive Control - Askari, Masoud; Moghavvemi, M.; Almurib, Haider Abbas F.; Ahmed Mohamed, Ahmed Haidar (IEEE, 2017)
This article addresses the stability of soft-constrained model predictive control. It is shown that the infinite horizon soft-constrained model predictive control problem can be solved as a finite horizon soft-constrained model predictive control problem if the prediction horizon is greater than an upper-bound. The contribution of this paper is a procedure to compute the prediction horizon upper bound which guarantees the stability. The proposed technique is verified using two simulation example. The second example (inverted pendulum) is verified through practical implementation. IEEE